Early Reading Movement through Read Aloud Training for Parents: A Community Development Project - Nita Novianti; Iyen Nurlaelawati; Temmy Widyastuti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
The National Literacy Movement is widely echoed in the school environment. On the other hand, literacy can also be developed at home for young children by parents. Reading together between parents and children is proven to be able to develop children's literacy. Herein, the Community Service activity which focuses on the initial read aloud training for parents is pivotal. The initial read aloud training aimed to train parents in a village in West Bandung Regency, West Java, to read storybooks to children. This activity was carried out in October 2018, involving 18 parents (mothers) with young children. Through this training, the involved parents showed an awareness, among mothers, of the importance of reading stories at home, selecting story books for children, and reading stories to and/or with children. Through this activity, it is hoped that parents can increase awareness of the importance of supporting literacy from an early age in children and practicing it at home. In addition, it is expected that there will be follow-up trainings such as reading assistance to parents